Ecumenical formation in the service of a renewed church - Pobee, J.S. (Ecumenical Review, 2001)
However important theology, formation, education, ministry, ecclesiology and ecumenism are, it is ecumenism that gives them perspective. They foster the develop- ment of the ecumenical imperative and a praxis founded in scripture, as well as the formation of persons to work in the service of ecumenism. Envisioning In some circles, especially in the World Council of Churches (WCC), envisioning is often understood as being “prophetic”. My aim is rather to forthtell, to articulate what we should or could be doing, so as to be viably church, faithful to the ecumenical imperative. Forthtelling engages with the contemporary reality of the context and lessons of history. Envisioning can also become ingenuous invention that does not exactly respond to the local contextual reality. For the vision to move peoples to live the ecumenical imperative, it must also be emotionally satisfying so that it challenges people to action. It should take seriously the language and idiom of the field of action. In the case of Africa, it may mean acquainting the people with the basic facts of ecumenism pre- cisely because ecumenical formation has been minimal.